Après Occupy Wall Street : construire la solidarité des endettés - Jean François Bissonnette (Politique et Sociétés, 2018)
This paper analyzes the historiography of the fur trade in the Canadian Subarctic region from the 16th to the 19th century to identify the constitutive elements and workings related to the articulation of the Indigenous traditional economy and the European commercial-proto industrial economic model. This system of articulation is constituted of the following: the MB-standard or made beaver; the credit system; a politics of gift; the introduction of manufactured goods. The paper explains at length the role of each of these four components and their systemic interaction, and aims to demonstrate that the Indigenous and European interpretations of this system are radically different and that the system has thrived on inter-miscomprehension; that the credit system and its loyalty inducement dimension was a crucial feature of the articulation of the two economies; and that this articulation and its components are key elements in the historical proletarization and territorial dispossession of the Indigenous peoples implicated in the fur trade industry, and has thus played a central role in the process of producing the colonial space on which contemporary Canada has been erected. À partir d’une analyse de l’historiographie de la traite des fourrures dans le subarctique canadien, cet article propose d’isoler et de caractériser le système d’articulation qui a permis dans le cadre du développement initial (XVIIe-XIXe siècles) de cette industrie d’arrimer l’économie indigène et l’économie européenne. L’article propose de définir ce système d’articulation par quatre dispositifs qui en seraient constitutifs : le MB standard ou made beaver, le crédit, les offrandes et les marchandises européennes. Offrant une description systématique du fonctionnement de ces dispositifs et une analyse de leur interaction, il s’agit à la fois de montrer que les interprétations indigène et européenne de ces dispositifs sont foncièrement différentes et ont fonctionné sur la base d’une « inter-mécompréhension » de fournir une illustration du ...